Pengaruh Konsentrasi Oksidasi NaIO4 dan NaCIO terhadap Pembentukan Gugus Karbonil pada Permukaan Selulosa sebagai Adsorben untuk Adsorpsi Logam Pb(SO4) - Sri Rahma; Jon Efendi (MASALIQ, 2026)
Heavy metal pollution, particularly lead (Pb), has become an urgent environmental issue, thereby requiring the development of effective and sustainable adsorbent materials. Cellulose, as a natural biopolymer, has potential as an adsorbent, but its adsorption capacity remains limited due to the low number of active groups on its surface. This study aims to evaluate the effect of sodium periodate (NaIO₄) and sodium hypochlorite (NaClO) concentrations on the formation of carbonyl groups in cellulose as a prospective adsorbent for Pb ions. This study used a laboratory experimental method by modifying cellulose through variations in NaIO₄ concentrations of 0.01 M and 0.02 M, followed by an oxidation process using NaClO. The modified products were characterized using Fourier Transform Infrared Spectroscopy (FTIR) to identify changes in functional groups after the oxidation process. The FTIR analysis results showed the presence of an absorption peak at a wavenumber of 1641 cm⁻¹, indicating the formation of carbonyl groups (C=O), as well as absorption peaks at 3333.9 cm⁻¹ and 1030 cm⁻¹, which respectively indicated the presence of O–H and C–O groups characteristic of cellulose. Increasing the oxidant concentration resulted in a higher carbonyl peak intensity, indicating an increased degree of oxidation on the cellulose surface. Thus, cellulose modification using NaIO₄ and NaClO was proven to increase the number of active groups on the cellulose surface. These findings contribute to the development of environmentally friendly biomass-based adsorbent materials with potential use for the adsorption of heavy metal ions, particularly Pb.